The Role of The Housewife in Managing Family Finances (Case Study in South Labuhan Batu Regency) - Anjani, Dina; Nasution, Yenni Samri Juliati; Syafina, Laylan (Yayasan Ilomata, 2024)
This research aims to examine the role of housewives with upper secondary education in managing family finances in Aek Torop Barat Hamlet KM 6, Asam Jawa Village, South Labuhan Batu Regency. This research use desciptive qualitative approach . The research site is located in Aek Torop Barat Hamlet KM 6 Asam Jawa Village, South Labuhan Batu Regency. Research time from May 2023 to November 2023. Primary data on field activities directly through interviews, asking questions and answers to informants. For the data taken, there were 2 (two) housewives who met the criteria determined by the author from 80 housewives. who work, have a monthly income, and have a secondary education or above (Bachelor's degree). Techniques used by researchers in this research survey is in form interview ( Interview ) For make it easier in the research. Interview is a communication process or an interaction which aims to collect something information Which appear through ask answer between a researcher with an informant or research subject (if the subject is man). so researcher do analysis data with the aim of making the data that has been obtained easier to use understood. This analysis uses theories related to The topic of this discussion is an attempt to observe the role of housewives in managing household finances. The research results show that housewives play an important role in financial planning, financial decision making, savings and investment. They face challenges in the form of unexpected expenses and inflation. Education influences financial understanding. Educated housewives are able to manage finances more planned and invest For period long Housewife households strive to increase financial literacy, use digital financial applications, and participate in financial development programs to overcome challenges. Despite facing various challenges, educated housewives have a significant role in managing household finances. With the knowledge of household financial management, the implementation and impact on day-to-day life will enable her to better manage her expenses, save for educational needs and have a much better financial life.